Acidogenesis of Pentose Liquor to Produce Biohydrogen and Organic Acids Integrated with 1G–2G Ethanol Production in Sugarcane Biorefineries - Peixoto, Guilherme [UNESP]; Mockaitis, Gustavo; Moreira, Wojtyla Kmiecik; Lima, Daniel Moureira Fontes; de Lima, Marisa Aparecida; Ferreira, Filipe Vasconcelos; Fuess, Lucas Tadeu; Polikarpov, Igor; Zaiat, Marcelo (MDPI, 2023)
Second-generation (2G) ethanol production has been increasingly evaluated, and the use of sugarcane bagasse as feedstock has enabled the integration of this process with first-generation (1G) ethanol production from sugarcane. The pretreatment of bagasse generates pentose liquor as a by-product, which can be anaerobically processed to recover energy and value-added chemicals. The potential to produce biohydrogen and organic acids from pentose liquor was assessed using a mesophilic (25 °C) upflow anaerobic packed-bed bioreactor in this study. An average organic loading rate of 11.1 g COD·L−1·d−1 was applied in the reactor, resulting in a low biohydrogen production rate of 120 mL·L−1 d−1. Meanwhile, high lactate (38.6 g·d−1), acetate (31.4 g·d−1), propionate (50.1 g·d−1), and butyrate (50.3 g·d−1) production rates were concomitantly obtained. Preliminary analyses indicated that the full-scale application of this anaerobic acidogenic technology for hydrogen production in a medium-sized 2G ethanol distillery would have the potential to completely fuel 56 hydrogen-powered vehicles per day. An increase of 24.3% was estimated over the economic potential by means of chemical production, whereas an 8.1% increase was calculated if organic acids were converted into methane for cogeneration (806.73 MWh). In addition, 62.7 and 74.7% of excess organic matter from the 2G ethanol waste stream could be removed with the extraction of organic acid as chemical commodities or their utilization as a substrate for biomethane generation, respectively.